Tialita obtida por moagem de alta energia e sinterizada pelas técnicas convencional e assistida por corrente elétrica - Lopes, Gabriel Do Lago (2016)
Many ceramic materials have great technological importance, such as tialite (β-Al2TiO5). This ceramic has excellent thermal shock resistance, high melting point, low thermal and electrical conductivity, low coefficient of thermal expansion and low wettability with molten non-ferrous metals, which allows its use in many applications, particularly in the refractory sector. However, this material may present structural instability and formation of microcracks after sintering. The purpose of this work includes the use of mechanical alloying (MA) of the tialite precursor powders (Al2O3 and TiO2), with addition of MgO, in order to obtain nanometric powders, which can improve the reactivity between these two oxides due the increase of surface área, whereas the addition of MgO to the system aimed at the stabilization of β-Al2TiO5 phase at room temperature. Thus, alumina (Al2O3) and titania (TiO2) were milled for four and eight hours in molar ratios of 45:45, 55:35 and 35:55, with 10 mol% of MgO. The milled powders were sintered in resistive oven (conventional sintering) and by sintering assisted by electric current (SPS – Spark Plasma Sintering). The characterization of milled powders was made by X-ray diffraction (XRD), showing that the adopted milling conditions were not sufficient for the formation of tialite at this stage, formation previously speculated; however, by the Scherrer equation were detected nanometric crystallite sizes for all investigated compositions. After compression by uniaxial pressing, drying and sintering, the samples were characterized by XRD, showing the formation of tialite for all investigated conditions, and the presence of unreacted precursors and spinels Al2MgO4 and Mg2TiO4. Also were conducted apparent porosity and apparent density measurements and the results indicated that the SPS technique promoted more efficient sintering, yielding in all compositions, densification levels higher than those obtained for the samples sintered conventionally. The Vickers microhardness measurements of the samples also showed the influence of sintering technique in this property, so that again the SPS technique provided higher values. However all the techniques presented microhardness values close to those observed in the literature (5 GPa). In all measurements and analyzes in this study it was possible to notice the influence of the composition and milling time, so that the alumina excess and the largest milling time provided superior results in terms of physical and mechanical properties in all cases, as well as lower crystallite sizes. The SEM-FEG micrographs confirmed the obtained results, showing a lower grain growth in the samples sintered by SPS and greater porosity in the samples sintered conventionally. Although the SPS technique to provide bodies with superior properties, conventional sintering also showed good results for the studied properties; in most cases with values close to SPS, especially in apparent density and microhardness. Thus, both techniques show great potential for studies in the refractory area, associated with mechanical alloying, which provides nanopowders.